LAYANAN PENDIDIKAN BAGI WARGA NEGARA INDONESIA DI ARAB SAUDI - Muhamad Murtadlo (Badan Litbang dan Diklat Kementerian Agama RI, 2018)
AbstractNowadays many Indonesian citizens work in Saudi Arabia and send their children to school in the country. Many are also prospective students seeking scholarships in Saudi Arabia. This study will examine how the actual form and practice of educational services for Indonesian citizens in Saudi Arabia and how the implications of such education services for Indonesia. The research was conducted by qualitative method through literature study and visitation. The study found that education services for Indonesian citizens in the country are still below expectations and in some ways below the standard. In addition, from the graduates, there is a tendency to develop a certain religious understanding that is somewhat different from the needs of moderate Islamic development (wasatiyah) in Indonesian country.Abstrak Hari ini banyak Warga negara Indonesia (WNI) yang bekerja di Arab Saudi dan menyekolahkan anaknya di negeri tersebut. Banyak juga para calon mahasiswa yang mencari beasiswa pendidikan di Arab Saudi. Penelitian ini iningi mengkaji bagaimana sebenarnya bentuk dan praktek layanan pendidikan bagi anak WNI di Arab Saudi dan bagaimana implikasi layanan pendidikan tersebut bagi Indonesia. Penelitian dilakukan dengan metode kualitatif melalui kajian kepustakaan dan visitasi. Penelitian menemukan bahwa layanan pendidikan bagi WNI di negeri tersebut masih dibawah ekspektasi dan dalam beberapa hal di bawah standar. Di samping itu dari lulusannya ada kecenderungan mengembangkan paham keagaman tertentuÂ yang agak berbeda dengan kebutuhan pengembangan Islam moderat (wasatiyah) di Indonesia.